2013
DOI: 10.1002/pc.22665
|View full text |Cite
|
Sign up to set email alerts
|

Novel chitosan-TiO2 nanohybrid: Preparation, characterization, antibacterial, and photocatalytic properties

Abstract: In this report, chitosan (CS) encapsulated titanium dioxide (TiO2) nanohybrid was prepared by chemical precipitation method. Fourier transform infrared spectroscopy (FT‐IR) and X‐ray diffraction (XRD) confirmed the formation of nanohybrid. Transmission electron microscopy (TEM) analysis showed the immobilization of TiO2 nanoparticles on the surface of CS. The nanohybrid was also characterized by thermogravimetric analysis (TGA) and zeta potential. The nanohybrid exhibited high photocatalytic activity as eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 33 publications
2
52
0
Order By: Relevance
“…Bacteria is also killed by high ROS produced by the photocatalytic process of TiO 2 , such as hydroxyl radical, superoxide, or hydrogen peroxide. 120 As a photocatalyst, titanium dioxide both oxidizes organic contaminants and damages microbial cells. Significant antibacterial performances are light activated from the nanomaterial of TiO 2 nanoparticle-based film.…”
Section: Photocatalytic Effectsmentioning
confidence: 99%
“…Bacteria is also killed by high ROS produced by the photocatalytic process of TiO 2 , such as hydroxyl radical, superoxide, or hydrogen peroxide. 120 As a photocatalyst, titanium dioxide both oxidizes organic contaminants and damages microbial cells. Significant antibacterial performances are light activated from the nanomaterial of TiO 2 nanoparticle-based film.…”
Section: Photocatalytic Effectsmentioning
confidence: 99%
“…The major weight loss was observed in second step between 250 and 500°C. It was reported that this weight loss was caused by decomposition of the polysaccharide and loss of (O-H) groups of TiO 2 dispersed in polymer matrices [37]. After 500°C there is no significant weight loss was observed.…”
Section: Characterization Studiesmentioning
confidence: 98%
“…1a-c respectively. TGA thermogram of PEG-titania showed the decomposition of PEG from 250 to 380 • C. The weight loss between 260 and 480 • C in the chitosantitania was attributed to the degradation of chitosan [21]. In P1-C3 titania, the initial weight loss from 50 to 250 • C was due to moisture vaporization and loss of other volatile species such as isopropanol and acetic acid [22].…”
Section: Thermogravimetric Analysismentioning
confidence: 99%